2015
DOI: 10.1373/clinchem.2014.233627
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Point-of-Care Human Chorionic Gonadotropin Testing: Can We Defuse This Ticking Time Bomb?

Abstract: Qualitative point-of-care (POC) 2 human chorionic gonadotropin (hCG) testing is routinely performed on urine samples obtained in the Emergency Department (ED) or before surgery to rule out pregnancy and prevent fetal injury or death. Because potentially harmful treatments are allowed to proceed on the basis of a negative hCG test result, falsenegative results can have disastrous consequences.We recently evaluated the performance of 11 common qualitative POC hCG devices and determined that 9 of the 11 devices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…6,9,22 However, we also found a broad range of serum values, consistent with prior study of the FDA's Manufacturer and User Facility Device Experience (MAUDE) database, which showed that most false negative results could not be attributed to the lower limit of detection or the hook effect. 23 Although some false negative results may reflect process errors, such as faulty documentation or deviations from assay procedures, previous studies have shown equivalent false negative rates between POC and laboratory urine testing. 4 Clinical decisions around pregnancy testing should incorporate the indication for the test, the implications of a false negative result, the pre-test suspicion for pregnancy, as well as test characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,22 However, we also found a broad range of serum values, consistent with prior study of the FDA's Manufacturer and User Facility Device Experience (MAUDE) database, which showed that most false negative results could not be attributed to the lower limit of detection or the hook effect. 23 Although some false negative results may reflect process errors, such as faulty documentation or deviations from assay procedures, previous studies have shown equivalent false negative rates between POC and laboratory urine testing. 4 Clinical decisions around pregnancy testing should incorporate the indication for the test, the implications of a false negative result, the pre-test suspicion for pregnancy, as well as test characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of hCGβcf (≥500,000 pmol/L) have previously been shown to cause false-negative results in certain qualitative POC hCG devices [4][5][6]. Previous studies have not carefully examined results from samples with hCGβcf concentrations between 50,000 and 500,000 pmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of hCGβcf (≥500,000 pmol/L) have been shown to cause false-negative results in certain pregnancy tests i.e. qualitative point-of-care (POC) hCG devices [4][5][6]. These pregnancy tests are often used to exclude pregnancy in women subjected to administration of radioactive isotopes for therapeutic or diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these studies call for further testing and/or modification of POC/ OTC pregnancy tests to ensure they are not susceptible to the excess βcf-hCG hook effect, [6] but it is important that the testing conducted is representative of true clinical scenarios that the assays might encounter. The studies discussed above have clearly demonstrated the hook effect can lead to false negative results and this effect has also been observed in clinical samples.…”
Section: Introductionmentioning
confidence: 99%